tRNA Derived smallRNAs: smallRNAs Repertoire Has Yet to Be Decoded in Plants - Sablok, Gaurav; Yang, Kun; Chen, Rui; Wen, Xiaopeng (Frontiers in Plant Science, 2017)
smallRNAs: Post-transcriptional Check points Post-transcriptional regulation represents an integrated network of array of RNAs, among which regulatory RNAs play a major role in deciphering and regulating the functional omics. Rise of next generation sequencing approaches have widely elucidated several classes of regulatory RNAs, often categorized into small non-coding RNAs and long non-coding RNAs (Heo et al. 2013) and have been shown to have epigenetically conserved or distinct functional roles in plants (Chan et al. 2004). Small non-coding RNAs have been profiled across a wide range of species and based on the type of the origin and function, they have been classified further into microRNAs (Zhang et al. 2006), siRNAs (Chan et al. 2004), piRNAs (Girard et al. 2006), isomiRs (Morin et al. 2008), circular RNAs (Sun et al. 2016), qiRNAs (Lee et al. 2009), and distinct class of tRNA derived smallRNAs (Hsieh et al. 2009). Origin of these non-coding class of RNAs have been attributed to several key events such as the coordination of the DICER-Like proteins (DCL-1) and methylated HEN1 for microRNA biogenesis and targeted action for transcriptional and translational repression, exonic and intronic splice sites variations and R-loop formation for circRNAs (Conn et al. 2017) and 3' cytosine additions or terminal modifications as a part of uridylation events have been implicated to be the major determinant for classifying isomiRs (Neilsen et al. 2012; Sablok et al. 2015). Among these classes, major focus till now has been leveraged on understanding the role and subsequent conservation target profiles of microRNAs